Rate of Decay of the Bernstein Numbers - Plichko, A. (Журнал математической физики, анализа, геометрии, 2013)
We show that if a Banach space X contains uniformly complemented l₂ⁿ 's then there exists a universal constant b = b(X) > 0 such that for each Banach space Y, and any sequence dn ↓ 0 there is a bounded linear operator T : X → Y with the Bernstein numbers bn(T) of T satisfying b⁻¹dn ≤ bn(T) ≤ bdn for all n. Показано, что для B-выпуклого сепарабельного пространства X, произвольного банахова пространства Y и любой последовательности dn ↓ 0 существует такой ограниченный линейный оператор T : X → Y и b > 0, что для всех чисел Бернштейна bn(T) оператора T имеем для любого n b⁻¹dn ≤ bn(T) ≤ bdn.